What Does “the RNA World” Mean to “the Origin of Life”? - Ma, Wentao (Life (Basel), 2017)
Corresponding to life’s two distinct aspects: Darwinian evolution and self-sustainment, the origin of life should also split into two issues: the origin of Darwinian evolution and the arising of self-sustainment. Because the “self-sustainment” we concern about life should be the self-sustainment of a relevant system that is “defined” by its genetic information, the self-sustainment could not have arisen before the origin of Darwinian evolution, which was just marked by the emergence of genetic information. The logic behind the idea of the RNA world is not as tenable as it has been believed. That is, genetic molecules and functional molecules, even though not being the same material, could have emerged together in the beginning and launched the evolution—provided that the genetic molecules can “simply” code the functional molecules. However, due to these or those reasons, alternative scenarios are generally much less convincing than the RNA world. In particular, when considering the accumulating experimental evidence that is supporting a de novo origin of the RNA world, it seems now quite reasonable to believe that such a world may have just stood at the very beginning of life on the Earth. Therewith, we acquire a concrete scenario for our attempts to appreciate those fundamental issues that are involved in the origin of life. In the light of those possible scenes included in this scenario, Darwinian evolution may have originated at the molecular level, realized upon a functional RNA. When two or more functional RNAs emerged, for their efficient cooperation, there should have been a selective pressure for the emergence of protocells. But it was not until the appearance of the “unitary-protocell”, which had all of its RNA genes linked into a chromosome, that Darwinian evolution made its full step towards the cellular level—no longer severely constrained by the low-grade evolution at the molecular level. Self-sustainment did not make sense before protocells emerged. The selection pressure that was favoring the exploration of more and more fundamental raw materials resulted in an evolutionary tendency of life to become more and more self-sustained. New functions for the entities to adapt to environments, including those that are involved in the self-sustainment per se, would bring new burdens to the self-sustainment—the advantage of these functions must overweigh the corresponding disadvantage.